Analysis of the charge state distribution produced in a 78Kr + 98Mo fusion evaporation reaction utilizing the MARA separator - Lightfoot, Alexandra (2016)
Experimental results on the charge state distribution of the fusion evaporation reaction 78Kr + 98Mo are presented. The data has been taken from the 1st commissioning run of MARA (Mass Analysing Recoil Apparatus). Data from the charge states of q = 29 − 33 were collected. Here, q represents the elementary charge describing the number of electrons removed from a neutral atom. Results show an expected gaussian distribution around the most probable charge, ̄q. A most probable charge state of ̄q = (27.99 ± 0.20) was obtained after fitting the data. The value of ̄q was lower than initially anticipated, which was mainly a result of a less than desired beam energy delivered on the day of testing.